Answer:
Step-by-step explanation:
The sum of the angles in a triangle is 180 degrees. This means that in triangle ABC,
Angle A + angle B + angle C = 180
Therefore,
6x - 1 + 20 + x + 14 = 180
6x + x + 20 + 14 - 1 = 180
7x + 33 = 180
Subtracting 33 from the left hand side and the right hand side of the equation, it becomes
7x + 33 - 33 = 180 - 33
7x = 147
Dividing the left hand side and the right hand side of the equation by 7, it becomes
7x/7 = 147/7
x = 21
Therefore
Angle A = 6x - 1 = 6 × 21 - 1
Angle A = 125 degrees
Angle C = x + 14 = 21 + 14
Angle C = 35 degrees.